Endothelial protein C receptor is overexpressed in colorectal cancer as a result of amplification and hypomethylation of chromosome 20q. (14th July 2017) - Lal, Neeraj; Willcox, Carrie R; Beggs, Andrew; Taniere, Philippe; Shikotra, Aarti; Bradding, Peter; Adams, Richard; Fisher, David; Middleton, Gary; Tselepis, Chris; Willcox, Benjamin E
Abstract: Endothelial Protein C Receptor (EPCR) is a Major Histocompatibility Complex homologue, with established roles downregulating coagulation and in endothelial protection. Expressed predominantly on endothelium, EPCR affects inflammatory, apoptotic and cell proliferation pathways by binding to activated protein C (APC). However, EPCR can also be expressed on cancer cells, although the underlying reasons are unclear. Moreover, although EPCR has been linked with chemosensitivity in lung cancer, its clinical significance in many tumours is unknown. Here, we explored its significance in colorectal cancer (CRC). Bioinformatic methods revealed EPCR overexpression in many epithelial cancers, which was confirmed on CRC epithelial tumour cells by immunohistochemistry. EPCR upregulation resulted from gene amplification and DNA hypomethylation, and occurred in concert with a cohort of neighbouring genes on chromosome 20q, a region previously implicated in chemoresistance. As in endothelial cells, EPCR reproducibly mediated ERK pathway activation in a model CRC cell line following APC treatment. However, EPCR knockdown studies failed to highlight compelling EPCR‐intrinsic impact on CRC cell phenotype, with limited effects on chemosensitivity and no effect on invasion observed, while EPCR appeared to decrease CRC cell migration. Consistent with these observations, differential EPCR expression did not influence response to chemotherapy in a human CRC cohort. Our results provide a compelling explanation for how EPCR is upregulated in diverse epithelial malignancies. They indicate that the clinical significance of EPCR varies across different tumour types. Furthermore, they raise the possibility that the prognostic significance of EPCR in certain tumours relates significantly to co‐upregulation of neighbouring genes on chromosome 20q. Therefore, efforts to exploit EPCR as a prognostic marker should be focussed on specific tumours, and in such scenarios EPCR‐co‐dysregulated genes may represent potential axes for therapeutic intervention.